Oropharyngeal colostrum immunotherapy and late-onset neonatal sepsis: an intervention study - Gabriela Cintra dos Santos; Tatiana de Oliveira Vieira; Camilla da Cruz Martins; Matheus Gomes Reis Costa; Graciete Oliveira Vieira (Revista Brasileira de Saúde Materno Infantil, 2024)
Abstract Objectives: to evaluate the effect of oropharyngeal colostrum immunotherapy in reducing cases of late-onset neonatal sepsis in preterm infants with very low birth weight. Methods: this is an intervention study, with a comparative analysis between the incidence of late-onset neonatal sepsis in the treatment group (in use of oropharyngeal colostrum immunotherapy) and the historical control group (newborns monitored in the same intensive care unit prior to the implementation of the oropharyngeal colostrum immunotherapy protocol). 81 premature babies born between 2016 and 2022 participated in the study separated according to whether or not they received oropharyngeal colostrum immunotherapy. The intervention consisted of eight daily applications of 0.2 mL of the mother's own raw colostrum to the newborns oral mucosa during the first seven days of life. Relative Risk and Absolute Risk Reduction and Number needed to Treat were calculated. Results: a protective effect of oropharyngeal colostrum immunotherapy against late neonatal sepsis was noted. Relative Risk: 0.43; CI95% = 0.21-0.91; Absolute Risk Reduction: 0.26; CI95%= 6.51 - 45.92 and Number Needed to Treat: 4 (2.17-15.34). Conclusion: administration of oropharyngeal colostrum proved to be a promising measure in protecting preterm newborns with VLBW against late-onset sepsis.